2008
DOI: 10.1016/j.marpolbul.2008.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Ocean urea fertilization for carbon credits poses high ecological risks

Abstract: The proposed plan for enrichment of the Sulu Sea, Philippines, a region of rich marine biodiversity, with thousands of tonnes of urea in order to stimulate algal blooms and sequester carbon is flawed for multiple reasons. Urea is preferentially used as a nitrogen source by some cyanobacteria and dinoflagellates, many of which are neutrally or positively buoyant. Biological pumps to the deep sea are classically leaky, and the inefficient burial of new biomass makes the estimation of a net loss of carbon from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 67 publications
0
35
0
Order By: Relevance
“…The stimulation of fish production by increasing phytoplankton biomass through CO 2 injection into specific ocean localities has also been proposed (Markels & Barber, 2001). However, ocean fertilization has been severely challenged because it would eventually destroy the local ecosystem (Bertram, 2010;Glibert et al, 2008).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…The stimulation of fish production by increasing phytoplankton biomass through CO 2 injection into specific ocean localities has also been proposed (Markels & Barber, 2001). However, ocean fertilization has been severely challenged because it would eventually destroy the local ecosystem (Bertram, 2010;Glibert et al, 2008).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…In the U tanks, urea was added as an organic nitrogen source. Our interest in the urea addition arose be cause it has been suggested that urea enrichment could preferentially lead to the dominance of cyano bacteria, pico eukaryotes and dinoflagellates (Glibert et al 2008, and references therein). We observed an increase in dinoflagellates towards the end (Table 2), and Synechococcus reached values higher than in the other treatments from Day 5 to Day 9 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Diatom growth has been reported to be dependent on silica availability (e.g. Allen et al 2005), and urea is thought to potentially select for some cyanobacteria and dinoflagellates because they have been found to preferentially use this molecule as a nitrogen source (Glibert et al 2008, Solomon et al 2010. Other algae are adapted to low nutrient concentrations, and they might bloom after oppor-tunistic species have depleted nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Ocean fertilization with nutrients is one of 2 potential methods of using the ocean to mitigate atmospheric CO 2 concentrations that have received both wide media interest (Young 2007) and considerable scientific scrutiny (Boyd et al 2007, Glibert et al 2008. (The other method is deep ocean CO 2 disposal; Parks 1999, Brewer et al 1999, Tamburri et al 2000.…”
Section: Historical Perspectivementioning
confidence: 99%